Determination of Product Life Cycle (PLC) for Formulation of Marketing Strategy UD. Matt Coffee Bondowoso - Pritantiwi, Sonnia; Fatimah, Feti; Hermawan, Haris (Garuda Prestasi Nusantara Consulting, 2023)
UD Matt Coffee is an agroindustry that produces various processed coffees, including green beans, roasted coffee, and ground coffee. Owner of UD. Matt Coffee took the initiative to establish this agro-industry to improve the welfare of smallholder coffee farmers in Sumberwringin District because the trading process for green bean is considered unprofitable and does not yet have added value. This study aims to determine and analyze the position of UD. Matt Coffee Arabica Coffee products uses a Product Life Cycle (PLC) approach based on the Polli and Cook method and to determine and analyze marketing strategies in developing its business based on the Product Life Cycle (PLC) for UD. Matt Coffee Arabica Coffee products. The analytical method used in this study is the Polli and Cook method to determine the position of UD. Matt Coffee Arabica Coffee products based on the product life cycle. The data collection technique used interview techniques with resource persons, namely the owner of UD. Matt Coffee. The results showed that at the growth stage through the Product Life Cycle approach at UD. Matt Coffee Bondowoso. The growth stage is characterized by rapid market acceptance and a substantial increase in UD. Matt Coffee Bondowoso’s profits and research results also show that the strategy adopted by UD. Matt Coffee Bondowoso in accordance with its position in the product life cycle, namely UD. Matt Coffee Bondowoso is looking for innovative strategies to maintain and even increase sales growth which includes market, product and marketing mix modifications. Keywords: Marketing, Product Life Cycle (PLC), Strategy.